Glomus tumors in the urinary tract: a rare case and literature review - Ramos Moreira Leite, Katia; Bogoevich, Ana Carolina Armiliato; Selegatto, Ivan Borin; Penachim, Thiago José; Neto, Wilmar Azal (International Journal of Pathology, 2024)
Background: The Glomus tumor is a rare mesenchymal tumor that predominantly affects the subcutaneous skin of the distal extremities. Solid organs are rarely affected, and the urinary tract has been the reason for isolated reports. This paper reviews the occurrence of glomus tumors in the entire urinary tract. Case Report: We report a case of a 56-year-old female, asymptomatic, with a 5.5 cm renal glomus tumor, and review the literature about the urinary tract involvement by this rare neoplasia. Conclusion: Glomus tumor mostly behaves as a benign lesion that rarely affects solid organs, being the kidney, the most affected organ in the urinary tract. It should be considered in the differential diagnosis of another renal cell tumor, especially those that are eosinophilic.